THE ROLE OF ELEMENTARY SCHOOL TEACHERS IN INTEGRATING ARTIFICIAL INTELLIGENCE CONCEPTS THROUGH SIMPLE CODING ACTIVITIES - Harol Hamonangan; Sri Yanti; Irma Desni; Hamka (PT. Jurnal Center Indonesia Publisher, 2026)
The rapid advancement of Artificial Intelligence (AI) presents both opportunities and challenges for elementary education. Teachers play a strategic role in preparing young learners to understand and adapt to technology critically, creatively, and ethically. This study aims to analyze the role of elementary school teachers in integrating AI concepts through simple coding activities, as well as to identify the strategies and challenges encountered during implementation. The research employed a qualitative descriptive approach, using interviews, classroom observations, and document analysis as data collection techniques. The findings reveal that teachers serve as digital learning facilitators, innovators in designing coding-based learning activities, and ethical guides who help students use technology responsibly. Simple coding activities effectively foster students’ logical thinking, creativity, and digital collaboration skills. However, limited technological infrastructure and insufficient teacher training remain major obstacles to sustainable implementation. Therefore, systemic support through educational policy, professional development, and adaptive curriculum design is essential. Integrating AI concepts through simple coding in elementary schools not only enhances digital literacy but also cultivates ethical awareness and social responsibility toward technology. With collaborative support from educators, institutions, and policymakers, elementary education can become a foundational stage for shaping a generation that is intelligent, creative, and morally grounded in the era of artificial intelligence